2017
DOI: 10.1111/jorc.12201
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional parameters as mortality predictors in haemodialysis: Differences between genders

Abstract: Depending on the gender, different parameters such as protein intake, potassium, phosphorus, body mass index and albumin are associated with mortality in patients undergoing HD. Albumin <3.5 g/dl is an independent mortality predictor in both genders, whereas a body mass index <23 kg/m is an independent predictor of death, but only in men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 40 publications
0
6
0
5
Order By: Relevance
“…Eriguchi et al [34] reported that very low and very high serum potassium levels were associated with higher all-cause mortality in incident PD patients, which can be partly explained by the impact of potassium on ventricular arrhythmogenicity. However, a study by Oliveira et al [35] in HD patients found that serum potassium was not a significant predictor of mortality. The findings from this study suggest that hypokalemia should be avoided in dialysis patients.…”
Section: Discussionmentioning
confidence: 93%
“…Eriguchi et al [34] reported that very low and very high serum potassium levels were associated with higher all-cause mortality in incident PD patients, which can be partly explained by the impact of potassium on ventricular arrhythmogenicity. However, a study by Oliveira et al [35] in HD patients found that serum potassium was not a significant predictor of mortality. The findings from this study suggest that hypokalemia should be avoided in dialysis patients.…”
Section: Discussionmentioning
confidence: 93%
“…Malnutrition significantly increases the risk of comorbidities and mortality during treatment for ESKD. Simple measures such as body mass index are good predictors of this increased risk . Patients are also at risk of other nutritional problems which are to some extent dependent on the nature of the dialysis treatment received.…”
Section: Nutritional Status and Clinical Outcomesmentioning
confidence: 99%
“…Malnutrition significantly increases the risk of co‐morbidities and mortality during treatment for ESKD. Simple measures such as body mass index are good predictors of this increased risk (Oliveira et al ). Patients are also at risk of other nutritional problems which are to some extent dependent on the nature of the dialysis treatment received.…”
Section: Nutritional Status and Clinical Outcomesmentioning
confidence: 99%